Digital euro safeguards - Protecting financial stability and liquidity in the banking sector - Claudia Lambert; Barbara Meller; Cosimo Pancaro; Antonella Pellicani; Petya Radulova; Oscar Soons; Anton van der Kraaij (European Central Bank (ECB), 2024)
A digital euro would provide the general public with an additional means of payment in the form of risk-free central bank money in digital form that is universally accepted for digital payments across the euro area. A digital euro would offer a wide range of financial stability benefits, including safeguarding the role of public money and strengthening the strategic autonomy and monetary sovereignty of the euro area in the digital era. It would be designed to have no material impact on financial stability or the transmission of monetary policy. This paper shows the usefulness of digital euro safeguards, such as holding limits, that would limit the impact of the introduction of a digital euro on banks' liquidity and on their reliance on central bank funding. To this end, it assesses how banks might respond to the introduction of a digital euro while seeking to maximise profitability and manage their risks for a range of holding limit scenarios. The results of the simulated impact on key liquidity metrics show that, with safeguards in place and on aggregate, the liquidity metrics of euro area banks would decline but remain well above regulatory minimums. In addition, the central bank funding ratios of euro area banks would not increase materially on aggregate and would remain contained overall.
Keywords: E42; E58; G21; 330; CBDC; digital euro; bank intermediation; financial stability risks